A High‐Gradient Magnetic Separator for Highly Viscous Process Liquors in Industrial Biotechnology. Issue 3 (29th January 2016) - Roth, Hans‐Christian; Prams, Andreas; Lutz, Michael; Ritscher, Jonathan; Raab, Moritz; Berensmeier, Sonja
Abstract: Following the demand for highly efficient processes in biotechnology, an innovative and cost‐effective permanent magnet‐based high‐gradient magnetic separator with static magnetic filters (SMF) is presented. The laboratory‐scale prototype has a high particle capacity and is characterized by an outstanding separation performance. Low‐cost magnetic nanoparticles (MNPs, hydrodynamic diameter 100 – 200 nm) were separated from highly viscous sucrose solutions. Losses of MNPs with filtrate remained very low. The in situ implementation of ultrasound technology during MNP‐backwashing yielded excellent MNP recovery efficiencies. By applying a non‐stick coating onto the SMF surface, the MNP recovery efficiency could be enhanced significantly compared to conventional SMFs. Abstract : The positive effect of ultrasound technology on particle recovery in a specially designed prototype of a high‐gradient magnetic separator is demonstrated. Separation efficiency of nanoscale magnetic particles was characterized for highly viscous sucrose model solutions. The particle backwashing process could be improved by the application of non‐stick coated static magnetic filters.